2017
DOI: 10.1021/acs.macromol.6b02526
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline Cryogels Supported with Poly(vinyl alcohol): Soft and Conducting

Abstract: The present contribution reports the single-step preparation of new type of soft macroporous conducting cryogels, a special type of hydrogels. Polyaniline/poly­(vinyl alcohol) cryogel was prepared by the oxidation of aniline hydrochloride in frozen reaction mixtures, in ice, containing a supporting polymer, poly­(vinyl alcohol). The cryogel used for illustration contained of polyaniline, poly­(vinyl alcohol) and 93 wt % of aqueous phase. It was macroscopically homogeneous and it had macroporous structure with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…As a kind of biodegradable and eco‐friendly materials, water‐soluble poly (vinyl alcohol) (PVA) has been widely used in various industrial applications, such as biodegradable materials, chemical engineering, and so on . The most important parameters influencing the physical properties of PVA are the molecular weight and alcoholysis degree .…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of biodegradable and eco‐friendly materials, water‐soluble poly (vinyl alcohol) (PVA) has been widely used in various industrial applications, such as biodegradable materials, chemical engineering, and so on . The most important parameters influencing the physical properties of PVA are the molecular weight and alcoholysis degree .…”
Section: Introductionmentioning
confidence: 99%
“…Until now,v arious strategies have been developed to fabricate conductive hydrogel for flexible electronic devices,i ncluding co-networks,b lends and self-assembly. [50][51][52][53][54][55][56][57][58] These strategies provide ab road perspective on designing and fabricating nanocomposite conductive hydrogels. We further divide theses trategies into several approaches:( i) electro or chemicalp olymerization of ac onducting monomer in ap refabricatedh ydrogel, (ii)mixing the conductive materials/monomers and hydrophilicp olymers/monomers followed by simultaneous or step-wise cross-linking to produce conductive hydrogels, and (iii)self-assembling the modified electrical conductive materials.…”
Section: Fabricationo Fc Onductive Hydrogelsmentioning
confidence: 99%
“…Great efforts have been made to improve the performance and durability of the materials used as electrodes and electrolyte of such devices. As low‐cost and flexible materials, conducting polymer (particularly polyaniline, PANI) based composite gels have received great attention to be used as the electrode material in supercapacitors . Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…As low-cost and flexible materials, conducting polymer (particularly polyaniline, PANI) based composite gels have received great attention to be used as the electrode material in supercapacitors. [7][8][9][10][11][12][13][14][15][16][17] Li et al have reported the supramolecular assembly of polyvinyl alcohol (PVA) and PANI for fabrication of flexible supercapacitors with 13.6 Whkg À 1 energy density. [9] In another work, graphene oxide was mixed with a composite gel to make supercapacitor electrodes with the specific capacitance of 438.8 Fg À 1 .…”
Section: Introductionmentioning
confidence: 99%